2012
DOI: 10.25103/jestr.051.06
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations using partial Porous Medium inside the Channels of Flat Plate Solar Water Collectors

Abstract: Commercial solar water heating collectors are usually oversized in order to satisfy a heat demand and this increases their manufacturing cost. It is possible to reduce the size of collectors if heat transfer from the channel walls to the working fluid is increased. To enhance the heat transfer to the working fluid a metal porous medium placed inside pipes. The presence of a metal porous medium made of aluminium or stainless steel results in the increase of the interface between the fluid and absorber, diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Authors in [4] reviewed applications of nanofluid in evacuated tube and flat plate solar collectors from efficiency, economic and environmental considerations and concluded that nanofluids offer a better alternative to conventional fluid. Authors in [5] presented theoretically and experimentally the enhancement of heat transfer to the working fluid with a metal porous medium placed inside pipes. The metallic mesh inserted in the collector, provided a higher water temperature compared to the conventional collector and it is the presence of the aluminum mesh inside the channels that distributes heat more evenly.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [4] reviewed applications of nanofluid in evacuated tube and flat plate solar collectors from efficiency, economic and environmental considerations and concluded that nanofluids offer a better alternative to conventional fluid. Authors in [5] presented theoretically and experimentally the enhancement of heat transfer to the working fluid with a metal porous medium placed inside pipes. The metallic mesh inserted in the collector, provided a higher water temperature compared to the conventional collector and it is the presence of the aluminum mesh inside the channels that distributes heat more evenly.…”
Section: Introductionmentioning
confidence: 99%
“…Amrutkar et al [8] designed a flat plate collector with different geometric absorber configuration at laboratory IS condition, and their study explained that for the same outlet temperature as that of conventional one we can reduce the area and number of tubes with change in absorber geometry. Iordanou [9] experimentally enhanced the heat transfer rate of flat plate collector with Aluminium/stainless steel porous medium insertion to the copper tubes. This results in increase in contact area of fluid to the absorber and also even distribution of heat to the fluid so that outlet temperature was increased.…”
Section: Introductionmentioning
confidence: 99%